Knowledge and Attitudes Toward Drug Hazards in Junior High School Students - Kecuk Tri Prasetya; Junaidi; Iman Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to determine the effect of drug knowledge and attitudes towards the dangers of drugs in elementary school students. This study used a descriptive research design using a cross-sectional approach. The research samples were students Depok Junior high school 1, West Java. The sampling technique in this study was taken by using the probability sampling method, namely the Simple Random Sampling method. The data collection instrument in this study was to use a questionnaire in the form of a number of written questions. Result. Of the 74 respondents, the results of the knowledge level test showed that 67 students of Depok Junior high school 1, West Java had a good level of knowledge of drugs (90.5%). 74 people (100%) had a positive attitude towards drugs and the results of the behavior test showed that the number of elementary school students with good behavior towards drugs was 63 people (85.1%). Conclusion. Students Depok Junior high school 1, West Java has a good level of knowledge, attitude, and behavior towards drugs.